PERANCANGAN PLTS ATAP ON GRID SYSTEM PADA KANTOR BADAN PERENCANAAN PEMBANGUNAN DAERAH PENELITIAN DAN PENGEMBANGAN KOTA PROBOLINGGO - Allan Ardiansyah; I Nyoman Setiawan; I Wayan Sukerayasa (Jurnal SPEKTRUM, 2021)
The rooftop on-grid PLTS system is commonly used by people from the household,commercial, to industrial sectors to reduce electricity bills from PLN. Based on PERMEN ESDM49 of 2018, the export value of electrical energy to the PLN electricity grid is 65%, and if energyexports are greater than energy bills, the rest will be stored and accumulated in the followingmonth. This is only valid for a maximum of 3 months, in the 4th month the remaining energyexport savings will be eliminated. Determining the right PLTS capacity makes the contribution ofPLTS in making bill savings more optimal. The office of BAPPEDA LITBANG Probolinggo Citywas used as the research location. The PLTS Scenario 1 design uses a capacity according tothe energy needs of the office, which is 21.6 kWp, and the PLTS Scenario 2 capacity is greaterthan the office energy requirement of 32.4 kWp. Based on the investment feasibility analysisusing the NPV, PI, and DPP methods, it shows that the Scenario 1 and Scenario 2 PLTSdesigns are feasible to run. PLTS Scenario 1 and Scenario 2 investment is Rp. 267,000,000and Rp. 395.85 million, respectively. The benefit of saving bills for 30 years of PLTS operation,in Scenario 1 is Rp. 406,863,069 or 152% of the total investment, while Scenario 2 is Rp.595,619,904 or 150% of the total investment.